Priority Activities in Child and Adolescent Tuberculosis to Close the Policy-Practice Gap in Low- and Middle-Income Countries - AFFOLABI, DISSOU (My University, 2022)
Over the past 15 years, and despite many difficulties, significant progress has been made to advance child and adolescent tuberculosis (TB) care. Despite increasing availability of safe and effective treatment and prevention options, TB remains a global health priority as a major cause of child and adolescent morbidity and mortality-over one and a half million children and adolescents develop TB each year. A history of the global public health perspective on child and adolescent TB is followed by 12 narratives detailing challenges and progress in 19 TB endemic low and middle-income countries. Overarching challenges include: under-detection and under-reporting of child and adolescent TB; poor implementation and reporting of contact investigation and TB preventive treatment services; the need for health systems strengthening to deliver effective, decentralized services; and lack of integration between TB programs and child health services. The COVID-19 pandemic has had a significant negative impact on case detection and treatment outcomes. Child and adolescent TB working groups can address country-specific challenges to close the policy-practice gaps by developing and supporting decentral ized models of care, strengthening clinical and laboratory diagnosis, including of multidrug-resistant TB, providing recommended options for treatment of disease and infection, and forging strong collaborations across relevant health sectors. Keywords: adolescent; child; national tuberculosis program; tuberculosis.
Keywords: Keywords: adolescent; child; national tuberculosis program; tuberculosis.